Calculation of Coal Resources Using the Circular Method at PT Manggala Alam Lestari Bayung Lencir - Rolitu Rolitu (Departemen Teknik Pertambangan FT UNP, 2024)
PT. Manggala Alam Lestari (PT. MAL) is a private national company that operates in the coal mining industry. PT.Manggala alam Lestary is located in Musi Banyuasin, Bayung Lencir district. As a coal-mining company, you must meet coal requirements to conduct resource calculations at the exploration stage before moving on to the mining preparation stage. The territory of IUP PT Manggala Alam Lestari is divided into V (five) mining blocks. However, Block IV, with an area of 150 hectares is currently not being calculated for coal resources, overburden, and stripping ratio since drilling activities are taking place on Block IV to sample coal thickness, overburden, and stripping ratio. The measured resource calculation for this coal is performed using the Circular method of block IV with a 100-meter radius, with data such as geological conditions on the ground and drilling data, and then the data is applied with supporting programs such as Software Surpac 6.6.2. Based on the data processing results, 1.579.428,13 tons of coal were measured using the circular method, as well as 1.067.573,57 m3 of overburden, or 1.708.117,71 tons.